Pentraxin-3 as a novel biomarker in predicting outcomes of nosocomial pneumonia: a prospective observational study - Isha Garg; Nishant Kumar Chauhan; Harsh Vardhan; Shrimanjunath Sankanagoudar; Naveen Dutt; Gopal Durgeshwar; Hariharan Iyer; Nikhil Kothari; Ravisekhar Gadepalli; Deepak Kumar (Monaldi Archives for Chest Disease)
Pneumonia, among all nosocomial infections, is known for its dismal prognosis, imposing substantial morbidity and mortality. While the diagnostic performance of various blood biomarkers has undergone scrutiny, their prognostic implications remain relatively unexplored. This study aimed to evaluate the prognostic significance of clinical factors, microbial etiology, and blood biomarkers, including procalcitonin, C-reactive protein (CRP), and pentraxin-3, in determining the outcome of nosocomial pneumonia. We enrolled 72 patients with microbiologically confirmed hospital-acquired pneumonia (HAP) or ventilator-associated pneumonia (VAP). Patient data comprising demographics, comorbidities, duration of hospitalization, isolated pathogen, and laboratory parameters, including CRP, procalcitonin, and pentraxin-3 levels, were compiled to assess their correlation with 28-day survival outcomes. The study included 58 VAP and 14 HAP patients. The mean age was 52.78±16.98 years, and the majority were males (68.06%). Out of 72, 30 (41.67%) died. Carbapenem-resistant Acinetobacter baumannii (44.44%) and Carbapenem-resistant Enterobacteriaceae (25%) were the most common isolated pathogens. On univariate analysis, male gender, smoking, opium addiction, underlying neurological condition as comorbidity, presence of septic shock, elevated blood urea, and serum pentraxin-3 levels were significantly associated with 28-day mortality. However, multivariate analysis of subgroup data revealed serum pentraxin-3 levels to be an independent risk factor for mortality in VAP patients. Serum pentraxin-3 levels may be a potential and superior prognostic marker compared to CRP and procalcitonin in predicting mortality in VAP patients.